Dampak Reformasi Administrasi Pemerintah terhadap Kinerja Aparatur Garis Depan (Suatu Tinjauan Teoritis & Empiris) - H.M. Edwar Juliartha (JIANA ( Jurnal Ilmu Administrasi Negara ), 2009)
Governance in effect is society servant, arranged governance don’t to service itself, but toservice society and creates condition that enables each society member develop its ability and itscreativity after reach aim with (Rasyid, 1988:139). Analogously thereto therefore aim form State issubject to be form governance that services people. Democratic governance wherewith governancewhich of people, by people and for means deep people can give service besting to people, as muchinvolve people and as much people enjoys it. Practically organizational public (governance) up tothis republic stand is positioned to service power instead of services costumer, namely people(Dwijawijoto, 2001:54). Its mean is apparatus governance is not again as society advocate, butbecomes “power” one has to be serviced by society. Even organizational governance which be-comes “ Gentleman ” and be not “ Servant ” society beget its fear insider takes initiative, piling itreport files, its castaway is time and be depleted fund which happens on Indonesian stricken crisisterm at media 1997.